Development of chitosan/silver sulfadiazine/zeolite composite films for wound dressing - Yassue-Cordeiro, Patricia Hissae (2019)
Biopolymeric films with silver sulfadiazine (AgSD) are proposed as an alternative to the occlusive AgSD-containing creams and gauzes, which are commonly used in the treatment of conventional burns. While the recognized cytotoxicity of AgSD has been reported to compromise its use as an antimicrobial drug in pharmaceuticals, this limitation can be overcome by developing sustained-release formulations. Microporous materials as zeolites can be used as drug delivery systems for sustained release of AgSD. The purpose of this work was the development and characterization of chitosan/zeolite composite films to be used as wound dressings. Zeolite was impregnated with AgSD before the production of the composite films. The physicochemical properties of zeolites and the films were evaluated, as well as the antimicrobial activity of the polymeric films and the cytotoxicity of the films in fibroblasts Balb 3T3/c. Impregnated zeolite exhibited changes in FTIR spectra and XRD diffraction patterns, in comparison to non-impregnated composites, which corroborate the results obtained with EDX-SEM. The pure chitosan film was compact and without noticeable defects and macropores, while the film with zeolite was opaquer, more rigid, and efficient against Candida albicans and some gram-negative bacteria. The safety evaluation showed that although the AgSD films present cytotoxicity, they could be used in a concentration-dependent fashion.